Pegylated Interferon Fractal Pharmacokinetics: Individualized Dosing for Hepatitis C Virus Infection - Jain, Mamta K. (American Society for Microbiology, 2013)
Despite recent advances in hepatitis C virus (HCV) therapeutics, the combination of pegylated interferon and ribavirin (PEGIFN/RBV) remains the cornerstone of treatment. Optimization and individualization of PEGIFN dosing could improve outcomes. Week one PEGIFN serum concentrations in 42 HCV genotype 1-infected patients treated with conventional PEGIFN/RBV were analyzed using multicompartmental pharmacokinetic models. For each patient, pharmacokinetic parameter estimates, weight, age, interleukin-28B (IL-28B) single-nucleotide polymorphism, CD4 count, baseline HCV RNA, gender, race, and HIV status were examined using classification and regression tree analysis to identify factors predictive of sustained viral response (SVR). Survival analysis was performed to compare the time to undetectable viral load in patients with and without the highest scoring predictor. PEGIFN concentrations varied at least 87-fold. Pharmacokinetics were best described by a two-compartment model with an 8.4-h absorption lag. Patient weight correlated with PEGIFN systemic clearance based on fractal geometry relationships. SVR was achieved in 36% of patients; a PEGIFN cumulative 1-week area under the curve (AUC) of ≤0.79 mg · h/liter scored highest in predicting poor response, followed by a weight of ≥93.7 kg. Patients with a PEGIFN AUC of >0.79 mg · h/liter achieved undetectable viral load more rapidly than those with a lower AUC (hazard ratio, 1.63; 95% confidence interval, 1.21 to 2.04). PEGIFN exhibits wide pharmacokinetic variability, mainly driven by patient weight, so that the standard dose may not reach levels needed to achieve SVR. Optimizing dose to patient weight and PEGIFN AUC in the first week offers a solution to improve SVR and to potentially shorten duration of therapy.